Short Communication Feeding Inter-Relationship of Caranx hippos (Linneaus), Chrysichthys nigrodigitatus (Lacepede), Ethmalosa fimbriata (Bowdich) and Mugil cephalus (Linneaus) in Lagos Lagoon, Nigeria - Fatimat, Adebiyi Adenike (Biological Sciences - PJSIR, 2010)
Study of the feeding inter-relationship of Caranx hippos, Chrysichthys nigrodigitatus, Ethmalosa fimbriata and Mugil cephalus in the Lagos Lagoon, Nigeria, revealed that algae and diatoms formed the main food items of the four fish species; other food items were crustaceans, molluscs and detritus. Utilization of nearly identical food items suggested inter-specific competition for food.